2014
DOI: 10.1186/1297-9716-45-67
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the tissue tropism to chicken oviduct epithelial cells between avian coronavirus IBV strains QX and B1648 are not related to the sialic acid binding properties of their spike proteins

Abstract: The avian coronavirus (AvCoV) infectious bronchitis virus (IBV) is a major poultry pathogen. A characteristic feature of IBV is the occurrence of many different strains belonging to different serotypes, which makes a complete control of the disease by vaccinations a challenging task. Reasons for differences in the tissue tropism and pathogenicity between IBV strains, e.g. a predilection for the kidneys or the oviduct are still an open question. Strains of the QX genotype have been major pathogens in poultry fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 22 publications
6
25
1
Order By: Relevance
“…5). These results are in line with the previously observed binding patterns of dimeric S1 of B1648 and QX to oviduct explants (Mork et al, 2014) and other IBV permissive cells, including tracheal epithelial cells and primary chicken kidney cells (Shahwan et al, 2013). Similarly, dimeric Beaudette S1 bound to chicken cells (Hesse et al, 2012), while trimeric Beaudette S1 was not sufficient for binding to trachea ( Fig.…”
Section: In Tissue Bindingsupporting
confidence: 91%
See 3 more Smart Citations
“…5). These results are in line with the previously observed binding patterns of dimeric S1 of B1648 and QX to oviduct explants (Mork et al, 2014) and other IBV permissive cells, including tracheal epithelial cells and primary chicken kidney cells (Shahwan et al, 2013). Similarly, dimeric Beaudette S1 bound to chicken cells (Hesse et al, 2012), while trimeric Beaudette S1 was not sufficient for binding to trachea ( Fig.…”
Section: In Tissue Bindingsupporting
confidence: 91%
“…This suggests that either these proteins bind with much lower affinities to the same sialic acid, or that they recognize yet other unidentified host factor, including specific sialic acids which might be not present on this array. While the results of Mork et al (2014) suggest that binding of recombinant dimeric S1 proteins of IBV strains with different pathogenicity to sialic acids is comparable, our studies using trimeric S1 proteins indicate that there might not only be differences in binding characteristics of different spikes (Fig. 4), but also differences in the attachment profiles of the spike protein to tissues from different animals.…”
Section: Sialic Acidsmentioning
confidence: 54%
See 2 more Smart Citations
“…Similarly, the results of this study showed that obvious positive immunohistochemical reactions developed not only in the cytoplasm of the tubular epithelial cells and in the mucous membrane of the ureters and collecting ducts in the kidney, and in the epithelial cells of the tracheal mucosa of the secondary bronchi at 5 dpc, but the viral antigens were also detected in the cecal tonsils. This result suggests a broad tissue tropism of strain ck/CH/LGX/111119, similar as that of its deduced parental LX4 genotype viruses (Benyeda et al, 2009;de Wit et al, 2011;Mork et al, 2014).…”
Section: Discussionsupporting
confidence: 62%